Exact equation

• Feb 9th 2010, 02:38 PM
steph3824
Exact equation
I already know this equation is not exact. The thing is, I never learned how to do partial derivatives so that is what I need help with. The equation is $(e^xsiny+3y)dx-(3x-e^xsiny)dy=0$
I know that the sign in the middle needs to be + so then you have $(e^xsiny+3y)dx+(-3x+e^xsiny)dy=0$.
Then M= $e^xsiny+3y$ and N= $-3e^x+e^xsiny$. So, I need help getting $M_y and N_x$.
• Feb 9th 2010, 03:04 PM
firebio
Quote:

Originally Posted by steph3824
I already know this equation is not exact. The thing is, I never learned how to do partial derivatives so that is what I need help with. The equation is $(e^xsiny+3y)dx-(3x-e^xsiny)dy=0$
I know that the sign in the middle needs to be + so then you have $(e^xsiny+3y)dx+(-3x+e^xsiny)dy=0$.
Then M= $e^xsiny+3y$ and N= $-3e^x+e^xsiny$. So, I need help getting $M_y and N_x$.

To do partial derivatives, just hold all other variables that u r not taking the derivative constant

So
$M_y = e^xcosy+3$
and
$N_x = -3e^x+e^xsiny$